A study on ownership structure and financial performance of listed beverage food and tobacco companies in sri lanka - Balagobei, S.; Velnampy, T. (Macrothink Institute, 2017)
The relevant literature suggests that ownership structure is one of the main corporate governance mechanisms influencing the scope of financial performance. The aim of this study is to investigate the relationship between ownership structure and financial performance of listed beverage food and tobacco companies for the period of 2010-2015. This study also examines the impact of ownership structure on financial performance. The sample consists of 10 listed beverage food and tobacco companies in Sri Lanka. In this study, data was collected from secondary sources and hypotheses are examined by using Pearson‟s correlation and regression analysis. The results reveal that ownership concentration and foreign ownership structure are positively correlated with financial performance of listed beverage food and tobacco companies while institutional ownership structure isn‟t significantly correlated with financial performance. It is also found that there is a significant impact of foreign ownership structure on financial performance. Higher the foreign ownership structure in listed beverage food and tobacco companies, the higher the financial performance which is preferable for the shareholders and it improves the wealth of companies.
Keywords: Corporate governance; Financial Performance; Institutional ownership; Ownership concentration